Stres, przemiany tożsamości i konsumeryzm — wyzwania współczesnej młodzieży - Orzechowski, Paweł (Studia Europaea Gnesnensia, 2014)
Every day, contemporary youngsters face limitations and exploit the possibilities offered by the global reality. The conditions which characterise the beginning of the 21st century are vastly different from the times in which their parents and grandparents grew up. It would be futile to look for any kind of order in the world today, be it political, moral or economic one. The young, who experience temporariness and constant change, have to develop their own measures of coping with post-modern challenges. The principal issue presented in this paper is the occurrence of information and relational stress. The fast pace of local migration, the overload of information, the weakening of social bonds and the relationships lasting “here and now” are the shameful markers of the lifestyle of young people. These are also constitutive traits which distinguish contemporary teenagers from their predecessors. In the subsequent section, the author considers excessive consumption as a modern form of cult. Finally, attention is drawn to the incoherent and continually evolving identity of individuals, who seek to determine their place within the contemporary social structures.